This Determinan Niat Wajib Pajak Perspektif Theory of Planned Behavior - Monika Bela Mahendra; Rachmawati Meita Oktaviani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This study analyzes the effect of the variables contained in the Theory of Planned Behavior, namely attitudes, subjective norms, perceived behavioral control on taxpayers' intentions. The sample in this study were taxpayers registered with MSMEs in Semarang Regency. The number of samples is 125 taxpayers. The sampling technique used was the solvin formula. The data analysis technique used is multiple linear regression analysis using SPSS version 26. The results of hypothesis testing indicate that attitudes have a direct effect on taxpayer intentions, while subjective norms and perceived behavioral control do not directly affect taxpayer intentions.